The Impact of Globalization on the Principle of Legality - Hafizhah, Annisa; Sukarja, Detania; Andriati, Syarifah Lisa (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2024)
The massive development of information and communication technology has accelerated the process of globalization and influenced various aspects of human life, including in the field of criminal law. This study aims to analyze how globalization affects the principle of legality. Using a normative legal approach, the data used in this study are sourced from primary, secondary, and tertiary legal materials obtained through literature studies. The transformation of the era challenges the relevance of the principle of legality in criminal law to protect society from crime. The emergence of various new types of crimes in the era of globalization is a threat to society while criminal law is hampered by the principle of legality to respond to these conditions quickly so that alternative solutions are needed to answer this challenge.